Research Progress of ORR Catalysts for Hydrogen Fuel Cell - Shi Chenyu; Song Minghu; Yang Jinxuanting; Zhang Zhaoyi (MATEC Web of Conferences)
Hydrogen fuel cells are attracting attention as devices to convert clean energy, among them, oxygen reduction reaction (ORR) platinum-based catalysts are essential in enhancing fuel cell performance. In the selection of catalysts for fuel cells, Pt has become the most suitable material on account of its unique catalytic properties. However, the cost of preparation and unstable catalytic properties have impeded the commercialization of Pt-based catalysts. This paper mainly introduces the latest progress of PtCo, PtNi, and PtFe series alloy catalysts, which have more active sites and can enhance the catalytic performance of ORR. Now there are still some shortcomings of the cumbersome preparation process and high cost, it can still show that this is a very promising direction, and these research results lay the foundation for the progress of platinum-based catalysts for ORR of hydrogen fuel cells. By optimizing the performance of platinum-based alloy catalysts, the efficiency and stability of hydrogen fuel cells can be significantly improved, thus promoting the commercial application of clean energy technologies. In addition, these studies provide important theoretical basis and technical support for reducing catalyst cost and simplifying preparation process and help accelerate the popularization and sustainable development of hydrogen fuel cells.